Articuler compétence linguistique et compétences professionnelles à l’université marocaine - Mohammed Lahlou (Recherches en didactique des langues et des cultures)
The university reform in Morocco raises questions about the identity and mission of teacher-researchers. Traditionally focused on the transmission of disciplinary knowledge and academic research, teachers are now called upon to take on a more versatile role, which includes preparing students for the demands of the job market. This shift requires them to balance the transmission of academic knowledge with the development of professional skills. To better define the contours of this new identity of the Moroccan teacher-researcher in language and culture, we conducted a field study aimed at assessing the role of languages in the acquisition of professional skills and career management within the entrepreneurial environment. This study leads to concrete proposals for university pedagogy, aiming to better align educational programs with the realities of the job market.